“If they were my son I’d have to apologize” : An Examination of Masculinity in Terrace House: Opening New Doors - Selonen, Lauri (My University, 2022)
This thesis combines Japan studies, reality television studies and gender studies in an attempt to map how masculinity is performed and represented in the reality television show Terrace House: Opening New Doors. Through a combination of qualitative close reading of the show and a review of prior theories of Japanese masculinity, this thesis seeks to produce a stance on whether the trajectories of hegemonic masculinity have been upset in the Japanese society and whether a shift to a more inclusive view of masculinity as suggested by Eric Anderson could be applied to the Japanese setting. The mundane, upper middle-class projective drama of the show provides us with a convenient mirror of assessing what kinds of practices of masculinity are acceptable in a decisively uncontroversial setting and thus perhaps in the society more widely. This thesis contends that in keeping with trends already identified in western settings, also the Japanese normative gender practice has had its boundaries moved and made accessible to more varied iterations of masculinity. It also contends that while successful masculinity has thus become societally less important, it has also become more difficult to achieve, suggesting that there exist distinct categories of ‘acceptable’ and ‘successful’ masculinity.
Keywords: Masculinity, Japan, Reality television, Gender, Terrace house